The Impact of Islamic Capital Market Literacy, Financial Behavior, and Income on the Interest to Invest in Islamic Capital Markets among Generation Z: - Zaenal Arifin; Muhamad Rizky Rizaldy (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the effect of Islamic capital market literacy, financial behavior, and income on the interest in investing in the Islamic capital market among generation Z. The research type and method used is quantitative research. The data used is primary data collected using an online questionnaire containing questions related to the variables, spread among Gunadarma University students as respondents. This study uses multiple linear regression analysis with a non-probability sampling technique assisted by statistical tools SPSS version 25. The results of this study indicate that partially Islamic capital market literacy variables (X1) and financial behavior (X2) have a significant effect on interest in investing in Islamic capital market. However, income (X3) has no partial effect on interest in investing. Meanwhile, simultaneously, the variables of Islamic capital market literacy, financial behavior, and income have an influence on interest in investing in the Islamic capital market. The results of this study emphasize the importance of increasing financial literacy to increase the involvement of Generation Z in the Islamic financial system, by intensifying socialization and education programs, in this case on the Islamic capital market. Keywords: Islamic Capital Market Literacy; Financial Behavior; Income; Interest to Invest; Gen Z